2021
DOI: 10.1038/s41598-021-81824-1
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric G-protein α subunit (RGA1) regulates tiller development, yield, cell wall, nitrogen response and biotic stress in rice

Abstract: G-proteins are implicated in plant productivity, but their genome-wide roles in regulating agronomically important traits remain uncharacterized. Transcriptomic analyses of rice G-protein alpha subunit mutant (rga1) revealed 2270 differentially expressed genes (DEGs) including those involved in C/N and lipid metabolism, cell wall, hormones and stress. Many DEGs were associated with root, leaf, culm, inflorescence, panicle, grain yield and heading date. The mutant performed better in total weight of filled grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…This is evidenced by genome sequences of 3000 rice genotypes ( Li et al, 2014 ) and growing functional genomics of N ( Li et al, 2018 ; Pathak et al, 2020 ; Mandal et al, 2022 ). Further, the recent NUE phenotype ( Sharma et al, 2018 , 2021 ; Pathak et al, 2021 ) growing quantitative trait loci (QTL) and genotyping ( Kumari et al, 2021 ) make rice an ideal target crop for NUE improvement. A recent simulation showed that $743 million per year could be saved by a 20% increase in rice NUE ( Langholtz et al, 2021 ), while the global expenditure in that direction is not even a tiny fraction of it.…”
Section: Introductionmentioning
confidence: 99%
“…This is evidenced by genome sequences of 3000 rice genotypes ( Li et al, 2014 ) and growing functional genomics of N ( Li et al, 2018 ; Pathak et al, 2020 ; Mandal et al, 2022 ). Further, the recent NUE phenotype ( Sharma et al, 2018 , 2021 ; Pathak et al, 2021 ) growing quantitative trait loci (QTL) and genotyping ( Kumari et al, 2021 ) make rice an ideal target crop for NUE improvement. A recent simulation showed that $743 million per year could be saved by a 20% increase in rice NUE ( Langholtz et al, 2021 ), while the global expenditure in that direction is not even a tiny fraction of it.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that G protein plays a vital role in regulating low-nitrogen stress in plants (Sun et al, 2014; Liang et al, 2018; Kaur et al, 2018; Pathak et al, 2021). However, the potential regulatory mechanism remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In general, following receptor-mediated activation, the heterotrimeric G protein transmits external signals to cells via various downstream cytosolic effectors to regulate biological processes (Bommert et al, 2013; Urano et al, 2015; Lee et al, 2017; Roy et al, 2019). AtGPA1 phosphorylates ABA-insensitive 1 ( ABI1 ) and phospholipase Dα1 ( PLDα1 ) to regulate ABA-dependent stomatal opening and closure in Arabidopsis (Roy et al, 2016; Hei et al, 2018; Pathak et al, 2021). The heterotrimeric G protein also interacts with plant-specific receptor-like kinases (RLKs) and receptor-like proteins (RLPs) to regulate multiple immune responses, shoot apical meristem development, and nodule formation (Bommert et al, 2013; Aranda et al, 2015; Pandey, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations